Solar energetic particles injected inside and outside a magnetic cloud - Rodríguez-García, L.; Gómez-Herrero, R.; Dresing, N.; Balmaceda, L. A.; Palmerio, E.; Kouloumvakos, A.; Jebaraj, I. C.; Espinosa Lara, F.; Roco, M.; Palmroos, C.; Warmuth, A.; Nicolaou, G.; et al. (EDP Sciences, 2025)
Context. On 2022 January 20, the Energetic Particle Detector (EPD) on board Solar Orbiter measured a solar energetic particle (SEP) event showing unusual first arriving particles from the anti-Sun direction. Near-Earth spacecraft separated by 17 degrees in longitude to the west of Solar Orbiter measured classic anti-sunward-directed fluxes. STEREO-A and MAVEN, separated by 18 degrees to the east and by 143 degrees to the west of Solar Orbiter, respectively, also observed the event, suggesting that particles spread over at least 160 degrees in the heliosphere.
Aims. The aim of the present study is to investigate how SEPs are accelerated and transported towards Solar Orbiter and near-Earth spacecraft, as well as to examine the influence of a magnetic cloud (MC) present in the heliosphere at the time of the event onset on the propagation of energetic particles.
Methods. We analysed remote-sensing data, including flare, coronal mass ejection (CME), and radio emission to identify the parent solar source of the event. We investigated energetic particles, solar wind plasma, and magnetic field data from multiple spacecraft.
Results. Solar Orbiter was embedded in a MC erupting on 16 January from the same active region as that related to the SEP event on 20 January. The SEP event is related to a M5.5 flare and a fast CME-driven shock of similar to 1433 km s(-1), which accelerated and injected particles within and outside the MC. Taken together, the hard SEP spectra, the presence of a Type II radio burst, and the co-temporal Type III radio burst being observed from 80 MHz that appears to emanate from the Type II burst, suggest that the shock is likely the main accelerator of the particles.
Conclusions. Our detailed analysis of the SEP event strongly suggests that the energetic particles are mainly accelerated by a CME-driven shock and are injected into and outside of a previous MC present in the heliosphere at the time of the particle onset. The sunward-propagating SEPs measured by Solar Orbiter are produced by the injection of particles along the longer (western) leg of the MC still connected to the Sun at the time of the release of the particles. The determined electron propagation path length inside the MC is around 30% longer than the estimated length of the loop leg of the MC itself (based on the graduated cylindrical shell model), which is consistent with the low number of field line rotations.